Panchromatic Light-Absorbing [70]Fullerene-Perylene-BODIPY Triad with Cascade of Energy Transfer as an Efficient Singlet Oxygen Sensitizer - Lifeng Dou; Yuanming Li; Lei Dong; Shuao Zhang; Yuanqi Wu; Yu Gong; Wei Yang; Hongdian Lu; Sane Zhu; Xiaoguo Zhou (Molecules, 2023)
A panchromatic light-absorbing [70]fullerene-perylene-BODIPY triad (C70-P-B) was synthesized and applied as a heavy atom-free organic triplet photosensitizer for photooxidation. The photophysical processes were comprehensively investigated by the methods of steady-state spectroscopy, time-resolved spectroscopy, as well as theoretical calculations. C70-P-B shows a strong absorption ability from 300–620 nm. Efficient cascading intramolecular singlet-singlet energy transfer in C70-P-B was confirmed by the luminescence study. The backward triplet excited state energy transfer from C70 moiety to perylene then occurs to populate 3perylene*. Thus, the triplet excited states of C70-P-B are distributed on both C70 and perylene moiety with lifetimes of 23 ± 1 μs and 175 ± 17 μs, respectively. C70-P-B exhibits excellent photooxidation capacity, and its yield of singlet oxygen reaches 0.82. The photooxidation rate constant of C70-P-B is 3.70 times that of C70-Boc and 1.58 times that of MB, respectively. The results in this paper are useful for designing efficient heavy atom-free organic triplet photosensitizers for practical application in photovoltaics, photodynamic therapy, etc.